IMPLEMENTATION OF THE PANCASILA STUDENT PROFILE STRENGTHENING PROGRAM FOR THE INDEPENDENCE OF CHILDREN AGED 5-6 YEARS IN KINDERGARTEN TRISULA 1 - Mahendra Puji Permana Aji; Yoyok Febrijanto (Suluh Adiluhung Publisher (SAPub), 2024)
Independence is a character that is important to develop in every human being from an early age, because independence is an ability related to the skill to make decisions about everything related to personal activities and needs. This research uses descriptive qualitative research methods and data is generated through observation, interviews, and documentation. The aim of this research is to determine the implementation of the program to strengthen the profile of Pancasila students for the independence of children aged 5-6 years. Based on the research results, it was concluded that by strengthening the profile of Pancasila students, children's independence increased, not only the aspect of independence but other aspects also increased, this is because children not only carry out and complete projects, but children also take part in providing ideas and ideas. about what activities the child wants in the project that will be held. So that children can express their ideas into something real and will also carry out activities according to their wishes and interests. These things can certainly improve aspects of development in children, one of which is the aspect of independence.